O controle judicial dos atos administrativos discricionários à luz dos princípios da razoabilidade e proporcionalidade: jurisprudência do Supremo Tribunal Federal e Superior Tribunal de Justiça - Araújo, Francisca Raili dos Santos (2025)
This scientific study examines the possibility of judicial review of discretionary administrative acts in light of the principles of reasonableness and proportionality, with special focus on the case law (jurisprudence) of the Federal Supreme Court (Supremo Tribunal Federal) and the Superior Court of Justice (Superior Tribunal de Justiça). The objective is to demonstrate that administrative discretion does not constitute an absolute power and must be exercised within the bounds of the law, guided by the aforementioned legal principles. This research adopted the deductive method, based on a literature review and an analysis of judicial decisions handed down by Brazil’s highest courts. From a doctrinal and jurisprudential standpoint, it was found that the principles of reasonableness and proportionality are indispensable tools for the Judiciary to verify, in the course of review, the compatibility of discretionary administrative acts with the Federal Constitution and the body of law as a whole, without encroaching on the Executive Branch’s authority. The conclusion is that judicial scrutiny of these acts ensures that administrative action is geared toward fulfilling the public interest and upholding fundamental rights, in accordance with the values and objectives of the Democratic Rule of Law